Eucaristia e poder sacerdotal - Barros, Solange Pereira (2007)
Our research seeks to understand the relationship established throughout history between Eucharistic ritual and priestly power, supported and legitimated by religious experiences and preserved until today. We intend to demonstrate a mutual dependency created between both concepts. Therefore, beginning from our object of research, religious power and its sacred authenticity we look first at Eucharist, beginning from its origin and symbolism as well as the process of transformation on the ways people comprehend and relate to this sacred symbol; secondly we look into religion and sacred power, the center of all theoretical construction, its institutionalization and evolution; finally we return to the Eucharist as the center of decentralized and shared power.